Asimetri Informasi pada Pembiayaan Pemilikan Rumah di Bank Syari’ah Mandiri - Alias Candra (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
Development Bank of Shari'ah is currently experiencing rapid growth. However this has not been accompanied by an understanding of the community of the operational system and the Shari’ah banking products. So also with the implementation of the product, it still has things that are Shari’ah can be debated. Particularly on financing products, is seen still there applying the asymmetry of information legally muamalah Islam is not permitted. Therefore, the need to study in-depth research for the sake of improvement of the system and the governance of Shari’ah banking that comply with Islamic jurisprudence. This article examines about things related to the asymmetry of information on financing products possession with the Akad Murabaha.